THE REACTION HUMAN BEHAVIOR TO NATURE IN DEAN DEVLIN’S MOVIE “GEOSTORM”: USING LITERARY ECOCRITICISM - Indrawan, Fajar; Nur, Sahril (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
The Reaction Human Behavior to Nature in Dean Devlin's Movie “Geostorm” Using Literary Ecocriticism. English Department, Faculty of Languages and Literature, Makassar State University. Determining the types of human-nature relationships and the natural disasters shown in Dean Devlin's film